Peran Manajemen Sumber Daya Manusia (SDM) Terhadap Kinerja dan Kualitas Pegawai Perbankan Syariah - Filzah Aulia; Siti Jamilah (Journal of Resources and Reserves (JRR), 2023)
This article discusses human resource management strategies to improve the quality and performance of sharia banking. Employees are a very important element in the operational activities of a company. Because sharia banking is still relatively new, one of the problems that arises is the shortage of experts in the field of sharia finance, both from academics and sharia banking practitioners. The approach used in writing this article is qualitative analysis using the literature review or literature study method. The sources that the author uses as references in writing this article come from several journals, articles and official websites. In this way, the author obtained relevant information from previous research discussing human resource management, and was able to compile several of these sources into an article and develop this research. The task of human resource management is to organize the human element well in order to obtain workers who are able to carry out their duties effectively in achieving company goals. Human resources are the driving force and assets of a bank. Without human resources, the bank will not progress and develop as planned in order to create high-quality and high-achieving employees.